2012
DOI: 10.22230/ijepl.2012v7n3a353
|View full text |Cite
|
Sign up to set email alerts
|

Juggling Educational Ends: Non-Indigenous Yukon Principals and the Policy Challenges That They Face

Abstract: This article reports on a 2008 study of non-indigenous principals working in Indigenous Yukon contexts. It examines the policy contexts in which Yukon principals are embedded, giving specific attention to how they address the tensions that exist as a result of operating at the intersections of micro, meso, and macro policy levels. The application of critical ethnography generates the opportunity to reveal and examine the tensions, distinctions, and contradictions underpinning their praxis, exposing the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…What we know from recent studies in Canada and Ontario is that policies are playing a more significant role in principals' work than in the past. We know generally that many school principals feel that their role is constrained by the number of initiatives imposed on a school [56][57][58]. Not only do principals in Ontario feel constrained by formal policy initiatives, but multiple policy initiatives within short time periods have also influenced how they do their work [59].…”
Section: Policiesmentioning
confidence: 99%
“…What we know from recent studies in Canada and Ontario is that policies are playing a more significant role in principals' work than in the past. We know generally that many school principals feel that their role is constrained by the number of initiatives imposed on a school [56][57][58]. Not only do principals in Ontario feel constrained by formal policy initiatives, but multiple policy initiatives within short time periods have also influenced how they do their work [59].…”
Section: Policiesmentioning
confidence: 99%
“…Another Chinese study revealed the curriculum reform had brought three conflicting cultural values to school leaders, the compliance culture, the examination culture and the new pedagogic culture (Yin, Lee, and Wang 2014). In India, nonindigenous principals working in indigenous schools appeared to struggle more with the instructional time, mandated external curricula and locally developed curricula (Blakesley 2012).…”
Section: Asiamentioning
confidence: 99%